Working the Image: Unearthing Aspects of Teachers’ Lives Through Arts-Engagement (LEARNing Landscapes, 2008)
This paper presents a research method and some of the results thereof that asked teachers to engage in a reflective arts inquiry. This inquiry led teachers to plumb the depths of their own unconscious and bring what lies beneath into conscious awareness, leading to deeper reflection and ontological knowing. The researchers suggest that such awareness leads to improvement of classroom life for teachers and their students.
Keywords: arts inquiry; uncounscious; ontological knowing; awareness; classroom improvement